Entrepreneurship: Entrepreneurs to Win Their Sustainable Competitive Advantages within Globalization Era - Gunawan, Lenny (Journal the Winners: Economics, Business, Management, and Information System Journal, 2011)
The purpose of this paper is to discuss globalization’s impacts on the world’s financial characteristics today. The findings inform that globalization promotes entrepreneurship because through globalization, financial markets have grown to be more efficient and flexible which can be seen through lower transaction costs, less binding financial regulations than before, less governments’ intervention within private sector and national economy structures, increasing number of market participants which leads to more access to information. Thus, globalization does create a better environment for entrepreneurs in achieving their competitive advantages and further to sustain them. This research was done by collecting data from papers, journals, modules, and internet databases. The data was analyzed and then concluded. Having applied the analytical process, it can be concluded that globalization does promotes entrepreneurship because it enables entrepreneurs to gain greater benefits at a certain degree of freedom than before in order to achieve and maintain their competitive advantages.